Thermoluminescence response of Ge-doped optical fiber dosimeters with different core sizes - Begumi, Mahfuza; A. K. M., Mizanur Rahman; Abdul Rashid, Hairul Azhar; Wan Yusof, Wan Abdullah; Mohd Noor, Noramaliza; Zulkifli, Mohd Imran; Muhamad-Yasin, S. Z.; Mat-Sharif, K. A.; Tamchek, Nizam; Mat Nawi, Siti Nurasiah; Wahib, Nor Fadira; Mohd Amin, Yusoff; et al. (IEEE (IEEEXplore), 2013)
Thermoluminescence (TL) properties of five different core diameter of 6 mol% germanium (Ge) doped optical fibers have been investigated for the purpose of TL dosimetry. The optical fiber dosimeter TL properties is compared with commercially available TLD-100 chips (LiF:Mg,Ti). Samples were irradiated using Cobalt-60 standard radiation source ranging from 1Gy to 10 Gy. These fibers show good linear dose response up to 10 Gy. Highest core diameter of Ge doped optical fiber (core 100 μm) provides the best response among all fibers. We observe the larger core fiber show better response than smaller core fiber. The relative sensitivity of 100 μm core optical fiber is 0.26 ± 0.04 with respect to TLD-100 chip.